BUILDING THE COMPETITIVENESS OF MICRO ENTERPRISES IN THE DIGITAL ECONOMY ERA THROUGH ENTREPRENEURSHIP EDUCATION, DIGITAL LITERACY, AND GOVERNMENT SUPPORT AS DRIVERS OF INNOVATION AND COMMUNITY WELFARE - Titin, Titin; Sulaeman, Moh. Muklis; Yustiyawan, Rachman Halim (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to comprehensively examine how entrepreneurship education, digital literacy, and government support contribute to building the competitiveness of micro enterprises in the digital economy era, as well as how these three elements collectively foster innovation and community welfare. The study employs a literature review method with a descriptive qualitative approach, collecting data from various academic sources such as Google Scholar and credible websites covering the period 1985–2025. Out of 50 initially identified articles, 39 were selected through a rigorous screening process based on thematic relevance, source credibility, and contextual suitability. The findings indicate that entrepreneurship education plays a vital role in shaping innovative mindsets and adaptive capabilities among micro-entrepreneurs, while digital literacy enhances their technological competence in facing the dynamics of digital-based markets. Government support—through policies, training programs, and the provision of digital infrastructure—acts as a catalyst that accelerates the transformation of micro enterprises toward a knowledge-based economy.